Development of a Piezoelectric-Based Hand-Pressure Generator for Green Technology Education - Damarwan, Eko Swi; Abrori, Aulia Farhad Tria Nur; Budiastuti, Pramudita; Wardhana, Alex Sandria Jaya (Circuit: Jurnal Ilmiah Pendidikan Teknik Elektro, 2026)
This study aims to develop a piezoelectric-based Hand-Pressed Generator as a green technology learning medium to support renewable energy competencies in vocational education. The research employed a Research and Development approach using the ADDIE model, which consists of analysis, design, development, implementation, and evaluation stages. The prototype was designed to convert mechanical energy from hand pressure into electrical energy using piezoelectric sensors integrated with rectifier circuits, a boost converter, and a microcontroller-based monitoring system. Functional testing was conducted by applying different pressure frequencies (30, 60, 90, and 120 presses per minute) to analyze the generated output voltage. The results indicate that the prototype successfully produced electrical output ranging from 0.7 VDC to 3.6 VDC, demonstrating a positive relationship between pressure frequency and generated voltage. Validation by subject-matter and media experts showed feasibility scores of 86.5% and 84.5%, respectively, while user feasibility testing among electrical engineering students reached 88.25%, indicating that the prototype is categorized as very feasible for learning. The findings suggest that the developed Hand-Pressed Generator can serve as an effective instructional medium for demonstrating micro-scale energy harvesting concepts and supporting green technology education in vocational learning environments.